Viral Load Dynamics in SARS-CoV-2 Omicron Breakthrough Infections. (30th July 2022) - Dewald, Felix; Detmer, Susanne; Pirkl, Martin; Hellmich, Martin; Heger, Eva; Herrmann, Maximilian; Lehmann, Clara; Zweigner, Janine; Klein, Florian
Abstract: To determine viral dynamics in Omicron breakthrough infections, we measured severe acute respiratory syndrome coronavirus 2 RNA in 206 double-vaccinated or boostered individuals. During the first 3 days following the onset of symptoms, viral loads were significantly higher (cycle threshold [Ct], 21.76) in vaccinated compared to boostered (Ct, 23.14) individuals ( P = .029). However, by performing a longitudinal analysis on 32 individuals over 14 days, no difference in the viral load trajectory was observed between double-vaccinated and boostered patients. Our results indicate that booster immunization results in a reduction in detectable viral loads without significantly changing viral load dynamics over time. Abstract : This study provides longitudinal data upon Omicron breakthrough infections in double-vaccinated and boostered individuals. While peak viral loads were reduced in boostered individuals, no difference was observed for the duration of SARS-CoV-2 detection between both groups.